Piezoelectric transducer for energy harvest and sensing - Jong, Januar (2009)
In recent year the finding of new source energy has been blooming very fast with the help of the advancement in technology. Piezoelectric has becoming more and more significant as the small and portable energy source. Mainly this energy harvested from piezoelectric devices is using the Lead Zirconate Titanate (PbZrTi) which is normally known as PZT. After the discovery of the electrical property of piezoelectric since the 18th century the usage of has increase from simple usage as a buzzer to sophisticated actuators and sensors. This report provides the experimental results of a novelty method of piezoelectric energy harvesting which is compared to the conventional method of piezoelectric energy harvesting. In general the conventional method of the energy harvesting is by flexing of the PZT thin film to create deformation of the PZT which produces electrical energy which could be stored in battery of super capacitor. In the experiments the new method used is using a hitting mechanism to create the deformation of the PZT and produce electrical energy. Through the experimental results it shows that the energy from hitting the PZT components actually produces higher energy output compared to the conventional method of flexing the PZT to create the deformation which produces the electrical energy. This experiment successfully proves that the hitting procedure could provide a higher output energy compare to the conventional method of energy harvesting.